Pengaruh Penerapan Metode Nht Terhadap Peningkatan Hasil Belajar Siswa Dalam Pembelaran Fiqih Kelas Viii Di Pondok Pesantren Darussalam Saran Kabun - Firda Aufa Yumni; Miftahir Rizqa; Risnawati Risnawati (CV. ITTC INDONESIA, 2025)
This study aims to determine the effect of the Numbered Heads Together (NHT) method on improving student learning outcomes in Fiqh learning. The background of this study is based on the low student learning outcomes in Fiqh subjects and the minimal use of learning methods that involve active student participation. This study uses a quantitative approach with a one-group pretest-posttest design, namely one class consisting of 38 students is used as a sample. The instrument used is a learning outcome test given before and after treatment. Data analysis was carried out through the Shapiro-Wilk normality test and the paired sample t-test. The results showed a significant increase in student learning outcomes after the application of the NHT method. The average pretest score of 60.74 increased to 75.79 in the posttest. The paired sample t-test showed a significance value of 0.000 <0.05, which means there is a significant difference between before and after treatment. Thus, it can be concluded that the NHT method has a positive effect on improving student learning outcomes in Fiqh subjects. This finding provides recommendations for educators to use the NHT method as an alternative in improving learning effectiveness.